Optimization of cutting parameter performance under MQL Nanolubricant approach during CNC Turning using Taguchi Method - Mohd Faizul Izwan, Ibrahim (Universiti Malaysia Perlis (UniMAP), 2021)
Access is limited to UniMAP community.